“It’s That Kind of Place Here”: Solidarity, Place-Making and Civil Society Response to the 2015 Refugee Crisis in Wales, UK - Taulant Guma; Michael Woods; Sophie Yarker; Jon Anderson (Social Inclusion, 2019)
This article examines the different ways in which local civil society has responded to refugees and asylum seekers in different parts of Wales in the wake of the recent “refugee crisis”. While the events of summer 2015 have generated a considerable amount of scholarly attention, including empirical accounts that look into local community responses to refugees and asylum seekers, the current research has tended to overlook the significance of place and the varied impact of “refugee crisis” across localities; this article aims to fill this gap in the existing research. It draws on findings from qualitative research carried out between 2017 and 2018 with refugee-supporting organisations based in three different locations in Wales. Taking a comparative look at these organisations, the article sheds light on the intensity and variation of civil society response in each of these localities, showing how this is informed by and closely interweaved with processes of place-making and place-framing, contributing to the reshaping of civil society networks and population profiles in these local areas. In conclusion, the article argues that humanitarian responses to “refugee crisis” can be understood not only as instances of hospitality and solidarity but also as practices of locality production.